The Effects of Interactive Briefing Methods for Breast Biopsy on Patients’ Anxiety Level - Esmerer, Emel; Kayadibi, Yasemin; Tekcan Şanlı, Deniz Esin; Gıca, Şakir; Şanlı, Ahmet Necati; Kılıç, Fahrettin; Yılmaz, Mehmet Halit (Cerrahpaşa Medical Journal, 2022)
Objective: To assess the effects of different patient briefing methods on patients’ anxiety levels and the efficiency of demonstration of the breast biopsy procedure using video animations and experienced patient interviews and to evaluate their potential applicability in clinical practice. Methods: In total, 156 patients were randomized into 4 groups based on the type of patient briefing method used: group 1(n = 37), patients with standard informed consent form; group 2 (n = 42), patients with a standard informed consent form and a video depicting breast biopsy procedure; group 3 (n = 32), patients with a standard informed consent form and video depicting breast biopsy procedure and interview; and group 4 (n = 45), patients with standard informed consent form and interview. Patients in all 4 groups filled the State-Trait Anxiety Inventory forms both pre and postoperatively. State-Trait Anxiety Inventory scores both pre and post-interventionally have been compared between these groups. Results: In each group and for all patient populations, the anxiety level significantly decreased in post-procedural state compared to pre-procedural tate. (P < .001). There was no significant different in anxiety levels between groups in pre-procedural state (P = .551), post-procedural state (P = .47), and general state (P = .869). When the change in anxiety level in pre and post-procedural state are assessed, no difference among groups was found (P = .384). Conclusion: Despite finding no difference in anxiety reduction level between different briefing methods like written informed consent, video, and interviews, we have received positive feedback from patients. We have shown the clinical utility of video briefing and interview, which are relatively new methods that increased patient cooperation. Cite this article as: Esmerer E, Kayadibi Y, Esin Tekcan Şanlı D, et al. The effects of interactive briefing methods for breast biopsy on patients’ anxiety level. Cerrahpaşa Med J. 2022;46(1):61-65.